Evaluation of the quality of life in patients undergoing low anterior resection or abdominoperineal excision with no preoperative radiation therapy for rectal cancer - Ponczek, Danuta; Nowicki, Andrzej; Zegarski, Wojciech; Banaszkiewicz, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2005)
Colorectal cancer (CRC), the most common type of malignant neoplasm of the digestive tract is a serious and growing problem not only in Poland but also all over the world. Most frequently, CRC is localized in the rectum. The usual treatment involves surgical resection, which may be completed with pre- or postoperative radio- or radiochemotherapy. The aim of the work was to assess the long-term quality of life in patients who underwent low anterior resection or abdominoperineal resection with no preoperative radiation therapy. Based on the analysis of medical records of 481 patients with colorectal cancer, a selection of patients eligible for the study was made. Conclusively, 102 patients were included in the study. 102 questionnaires with additional information and telephone contact number were distributed by post. 78 patients returned the questionnaires (76.5%). The data was collected using a QLQ-C30 questionnaire for assessment of quality of life in cancer patients and a colorectal cancer module QLQ-CR38. Additionally, a questionnaire of socio-demographic data was used. This questionnaire involves such factors as age, gender, education, place of residence, material status, family relations, support, coexisting diseases, complementary and alternative treatment and length of time after operation. Based on the analysis of the results, the following conclusions were drawn: 1. Low anterior resection and abdominoperineal excision as main methods of surgical intervention in colorectal patients influence the long-term quality of life in a comparable way. 2. Low anterior resection may give a chance for a better quality of life but it is not guaranteed.